Rural gender relations [ issues and case studies - Bock, Bettina B. [ (Bettina Barbara] , 1960-; Shortall, S. (CABI Publishing, 2006)
This book explores the gender effects of the current transformation of agriculture and rural life. It presents a comparative perspective on key research themes of rural gender relations, with each section beginning with a comprehensive overview. Five thmes are addressed: (1) developments in rural gender theory and research methodology; (2) changes in farm households; (3) patterns of rural migration; (4) the impact of national and international policies; (5) and the construction of gender identities as a result of rural changes. This book will be of interest to advanced students and researchers of rural sociology, agrarian change, rural geography and gender studies. The book has 23 chapters and a subject index.